Maternal Dietary Inflammatory Potential and Quality Are Associated with Offspring Asthma Risk over 10-year Follow-up: The Lifeways Cross-Generation Cohort Study (OR35-05-19). (13th June 2019) - Chen, Ling-Wei; Navarro, Pilar; Shivappa, Nitin; Mehegan, John; Murrin, Celine; Hebert, James; Kelleher, Cecily; Phillips, Catherine
Abstract: Objectives: Asthma is the most common childhood chronic health condition. Maternal antenatal diet has been associated with offspring asthma risk, but long-term offspring follow-up (> 5 years) and studies investigating maternal whole diet quality and inflammatory potential are rare. We thus aimed to elucidate these associations using data from a prospective birth cohort study in Ireland. Methods: Early pregnancy dietary data were obtained using a validated food frequency questionnaire. The Dietary Inflammatory Index (DII®) is a literature-based method to quantify dietary inflammatory potential; a higher score indicates a more pro-inflammatory diet. The Healthy Eating Index (HEI) 2015 contains 9 adequacy and 4 moderation components; a higher score indicates better dietary quality. Doctor-diagnosed offspring asthma status (general practitioner or parent reports) for the first 10 years of life was collected at 3-, 5-, and 9-year follow-up. A total of 862 mother-child pairs (singleton pregnancy with information on maternal diets and offspring asthma status) were included. The longitudinal association between maternal energy-adjusted DII and HEI scores and offspring asthma status was assessed using generalized estimating equations. Missing covariates were accounted for using 20 multiple imputations. Results: Cumulative offspring asthma incidence was 21% over the 10-year period. In the main models, adjusted for maternal lifestyle and sociodemographic factors, a higher DII score was associated with higher risk of offspring asthma (OR: 1.34; 95% CI: 1.10, 1.65; P = 0.004; per 1 SD score increment), while a higher HEI score was associated with lower risk (OR: 0.77; 95% CI: 0.64, 0.93; P = 0.006). Results persisted with further adjustment for childhood factors (breastfeeding, childcare attendance, dietary quality, active and sedentary time), damp in house and parental asthma history. Similar associations were observed when DII and HEI scores were modeled in quartiles (both P-trends < 0.05; Figure 1). Conclusions: Our results suggest that a pro-inflammatory and low-quality diet during pregnancy is associated with higher risk of offspring asthma. These results add to the knowledge base for informing maternal pregnancy dietary recommendations to optimize offspring health. Funding Sources: Irish Health Research Board, Science Foundation Ireland, and the European Union. Supporting Tables, Images and/or Graphs: